Aesthetic advertising image in the women's magazines covers: ليلى علي رجب العبيدي (Al-Academy, 2016)
In life in general and in the press, especially the success of a particular message depends heavily shipments carried by, and images idyllic suggestive, how many meanings that reaching an audience, and is the magazines and one of those media that target a broad audience, trying to please Him and the acquisition of his attention through a form of aesthetic granted pleasure and satisfaction from this point of view, read image ad as Date pure incident of everyday life, and here was placed this research about the aesthetic image advertising in the covers of women's magazines, which has been briefing them through the Four Seasons included in the search, was the first chapter Batarh systematic talked about problem Find the placing on the form of questionable what aesthetic modes of check image advertising in women's magazines , Which will be the goal of this research, which is the need of the needs of the students and those interested in this specialty is the design layout and finished chapter identify the most important terms that came in its title, and then the second quarter Bembagesh three, was the first topic look philosophical quick about aesthetic image began attempts rights firstto express his concerns that have become an integral part of contemporary human life , Then the second part, which talked about the image ad .. between the job and innovation and what are the foundations upon which the image to be innovative and check attraction and fascinate and credibility at the same time, functions and aesthetic news and hold it connotations of expressive and the resort of magazines to use image advertising to influence the recipient and convince him, and Maitalq outthe ability of the marketing and promotion, and then enter the third section, which dealt with covers of women's magazines and her money from the privacy of all other magazines in being treated with a class (women) are characterized by Brhafah sense and the ability consumer for so must provide the elements of attraction and persuasion to enable the marketing materials for this class, whether newsor cultural, Then came the researcher three indicators resulting from the theoretical framework related to image advertising, color and check the foundations of design of the suit, unity, harmony and rhythm to get into the casing attractive is the identity of the magazine, which he represents, and came third quarter pregnant research procedures and the reasons for selecting the sample by clicking the extensive research and analysis of the sample according to the indicators frameworktheoretical and exit outcomes which included:1 - Play's advertising in women's magazines play an important role in achieving the attraction of being an aesthetic element breaking the deadlock and aims to influence and operates the largest area of the cover.2 - Color is one of the important elements in the design press, and plays an important role aesthetically and functionally by directing the reader's eye movement on the cover as he has psychology effects and suggestive with weights.3 - be for Altibograveh elements of Article print clarity and how to show the importance of attracting the receiver to the content of the magazine and therefore verify respond in acquisition. Has also been recording the conclusions drawn from the research, and the inclusion of sources with pictures included extension sample (1-6) of the flower magazine covers the Gulf.